Problem of Companies Financial Analyses Derivatives Evaluation (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This article concentrates on derivatives evaluation in financial report. As result to search, derivatives have negative affection and positive affection practically. Derivatives have cost in current time but return in future is not clear because of expecting possibility. In spite of its cost it must give value to increase assets value or reduce liabilities value or reduce cost or reduce tax or make profit at time of making financial report. Negative affection comes from transfer risk of loss which transfers loosing responsibility it added new type of risk. By comparing between derivatives and traditional choices to face risk, there is different in evaluation as result to degree of responsibility, source of its value, Liquidity, currency risk, product market price risk, credit risk and linked with other selling contract risk. Searcher recommended to reduce ignorance by explains the real looser and looser ability to buy loss which limit derivatives transfer loss in order to make financial report useful. Its difficulty comes from promising to give product and promising to buy price in future regardless of loss which needs grantee to apply promising or give suitable compensation. Some things consider as standards may not accept expecting rules for pricing as some currencies price which just apply by monetary policy.